Modulation of spermidine and spermine levels in maize seedlings subjected to long-term salt stress - Jiménez-Bremont, Juan F (Plant physiology and biochemistry : PPB, 2007)
Salinity is one of the major abiotic stresses affecting plant agriculture worldwide. Polyamines, a group of aliphatic amines, are known to accumulate under salt stress conditions in different plant systems, resulting in presumed protective effects, acting as free radical scavengers, stabilizing cellular membranes and maintaining cellular ionic balance under these conditions. In the present study, we measured the polyamine content in maize leaves of semi-hydroponically grown seedlings subjected to 1 and 7 days of salt stress. We observed that the maize plants tend to maintain or accumulate the levels of spermidine and spermine, while putrescine levels fluctuate depending on the NaCl concentration. The effect of salt stress on the expression of the main genes involved in polyamine biosynthesis was also assessed. Our data show a time and NaCl dependent regulation of the Zmspds2 and Zmspds1 genes, suggesting that the former might be hyperosmotic responsive while the later NaCl responsive. Interestingly, the maize adc, Zmspds1 and Zmspds2 genes are regulated at the transcriptional level by the plant growth regulator abscisic acid. A connection between polyamine metabolism, abiotic stress and abscisic acid is discussed